Histopathological evaluation of Non-Neoplastic and Neoplastic Lesions of Uterine Cervix at tertiary care centre - Dr. Supriya B.R.; Dr. Ragini Patel; Dr. Manisha Patel (Tropical Journal of Pathology and Microbiology, 2019)
Background: Uterine cervix is common specimen from gynecological department with non-neoplastic and neoplastic lesions. Most cervical cancers can be detected at pre-invasive state with an adequate screening and treated appropriately thus preventing overt progression to full blown cancer and hence decreasing morbidity and mortality. Carcinoma of cervix is a preventable tumor and if good effort given in detecting preinvasive lesion one can give definite treatment at earliest. Objectives: To evaluate the histopathological diagnosis of a biopsy of cervix in women with unhealthy cervix. Also, to study the agerelated, incidence and the incidence of various nonneoplastic and neoplastic lesions of the cervix. Methodology: It is a cross sectional study. Institutional Ethics committee permission was taken prior to start of the study. Pertinent clinical history like age, significant family and personal history, history of other diseases was taken. Cervical biopsy specimens collected from histopathology section and grading of cervical lesions was done based on the proportion of stained cells and the intensity of staining. Statistical analysis was done. The data were tabulated and frequencies and percentages were calculated. Observations: The common age group was 41-50 years (37.50%) followed by 31-40 years of age (26.25%). The symptoms with which patients presented were vaginal bleeding (52.50%) followed by white discharge per vagina (16.25%) and menorrhagia (12.50%). The premalignant lesions were seen in 12 cases (15.0%) and malignant lesions in 68 cases (85.0%). Among them 64 malignant tumours were epithelial in origin. As per microscopic examinations squamous cell carcinoma was diagnosed in 61 cases (93.75%), followed by 2 cases (3.13%) of adenocarcinoma, and 1 case (1.58%) of adenosquamous carcinoma and 1 case (1.54%) of rhabdomyosarcoma. Conclusion: Cervical cancer continues to be the most common cancer of females in developing countries. One of the most significant advances in the management of cervical neoplasms has been the realization that cervical intraepithelial lesions behave as progressive stages of a biologic continuum towards the development of invasive cancer.